Community engagement to inform development of strategies to improve referral for hypertension: perspectives of patients, providers and local community members in western Kenya - Violet Naanyu; Benson Njuguna; Hillary Koros; Josephine Andesia; Jemima Kamano; Tim Mercer; Gerald Bloomfield; Sonak Pastakia; Rajesh Vedanthan; Constantine Akwanalo (BMC, 2023)
Abstract Background Hypertension is the leading cause of death and disability. Clinical care for patients with hypertension in Kenya leverages referral networks to provide basic and specialized healthcare services. However, referrals are characterized by non-adherence and delays in completion. An integrated health information technology (HIT) and peer-based support strategy to improve adherence to referrals and blood pressure control was proposed. A formative assessment gathered perspectives on barriers to referral completion and garnered thoughts on the proposed intervention. Methods We conducted a qualitative study in Kitale, Webuye, Kocholya, Turbo, Mosoriot and Burnt Forest areas of Western Kenya. We utilized the PRECEDE-PROCEED framework to understand the behavioral, environmental and ecological factors that would influence uptake and success of our intervention. We conducted four mabaraza (customary heterogenous community assemblies), eighteen key informant interviews, and twelve focus group discussions among clinicians, patients and community members. The data obtained was audio recorded alongside field note taking. Audio recordings were transcribed and translated for onward coding and thematic analysis using NVivo 12. Results Specific supply-side and demand-side barriers influenced completion of referral for hypertension. Key demand-side barriers included lack of money for care and inadequate referral knowledge. On the supply-side, long distance to health facilities, low availability of services, unaffordable services, and poor referral management were reported. All participants felt that the proposed strategies could improve delivery of care and expressed much enthusiasm for them. Participants appreciated benefits of the peer component, saying it would motivate positive patient behavior, and provide health education, psychosocial support, and assistance in navigating care. The HIT component was seen as reducing paper work, easing communication between providers, and facilitating tracking of patient information. Participants also shared concerns that could influence implementation of the two strategies including consent, confidentiality, and reduction in patient-provider interaction. Conclusions Appreciation of local realities and patients' experiences is critical to development and implementation of sustainable strategies to improve effectiveness of hypertension referral networks. Incorporating concerns from patients, health care workers, and local leaders facilitates adaptation of interventions to respond to real needs. This approach is ethical and also allows research teams to harness benefits of participatory community-involved research. Trial registration Clinicaltrials.gov, NCT03543787, Registered June 1, 2018. https://clinicaltrials.gov/ct2/show/NCT03543787